Single-Cell Atlas Reveals Fatty Acid Metabolites Regulate the Functional Heterogeneity of Mesenchymal Stem Cells - Xie, Jiayi; Lou, Qi; Zeng, Yunxin; Liang, Yingying; Xie, Siyu; Xu, Quanhui; Yuan, Lisha; Wang, Jin; Jiang, Linjia; Mou, Lisha; Lin, Dongjun; Zhao, Meng (Frontiers in Cell and Developmental Biology, 2021)
Bone marrow mesenchymal stem cells (MSCs) are widely used clinically due to their versatile roles in multipotency, immunomodulation, and hematopoietic stem cell (HSC) niche function. However, the cellular heterogeneity limits MSCs in the consistency and efficacy of their clinical applications. Metabolism regulates stem cell function and fate decision, however, how metabolites regulate the functional heterogeneity of MSCs remains elusive. Here, using single-cell RNA sequencing, we discovered that fatty acid pathways are involved in the regulation of lineage commitment and functional heterogeneity of MSCs. Functional assays showed that fatty acid metabolite, butyrate, suppressed the self-renewal, adipogenesis, and osteogenesis differentiation potential of MSCs with increased apoptosis. Conversely, butyrate supplement significantly promoted HSC niche factor expression in MSCs, which suggested that butyrate supplement may provide a therapeutic approach to enhance their HSC niche function. Overall, our work demonstrated that metabolites are essential to regulate the functional heterogeneity of MSCs.